Polymers Enhancing Bioavailability in Drug Delivery, 2nd Edition - Fernandes, Ana Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue provides an update on the state of the art and current trends in polymeric drug delivery systems specifically designed for improving drug bioavailability. The multiple contributions received further strengthen the role of polymers in modern drug delivery and targeting, illustrating the different approaches possible and unveiling what the future may bring.